Reactualizing Religious Moderation in Strengthening the Spirit of Diversity in Indonesia’s Multicultural Society - Muhammad Fikri Fardiansyah; Rikza Syahrial Kurniawan; Divan Ade Prayogo; Rahmadini Mulya Aisah; Achmad Muhibin Zuhri (JURNAL AT-TURAS, 2026)
Indonesia is a multicultural country characterized by diversity in religion, ethnicity, culture, and language. While this diversity represents a major social asset, it also has the potential to generate conflict when it is not managed through inclusive and constructive approaches. This study aims to analyze the urgency of re-actualizing religious moderation as a strategy to maintain national unity and strengthen the spirit of diversity in Indonesian society. This research employs a qualitative literature review method by examining books, academic journal articles, and recent policy documents related to religious moderation, multiculturalism, and the socio-religious dynamics of Indonesian society. The analysis is conducted using a thematic content analysis approach to identify key concepts, patterns of discussion, and conceptual gaps in recent studies. The findings indicate that religious moderation functions as a cultural and social framework that balances religious commitment with national values and social harmony. The re-actualization of religious moderation requires an integrative strategy through three main domains: strengthening value-based education in formal institutions, promoting inclusive da'wah that encourages dialogue and tolerance, and developing digital literacy to counter intolerance and extremist narratives in online spaces. These findings highlight that sustaining unity in a multicultural society depends on the collective ability to manage differences through inclusive, dialogical, and ethically grounded practices. Therefore, religious moderation should be understood not only as a theological discourse but also as a practical framework for fostering social cohesion and maintaining diversity in the contemporary era.